Transformation behavior and superelastic properties of Ti-Ni-Ag scaffolds prepared by sintering of alloy fibers. (August 2018) - Li, Shuanglei; Kim, Yeon-wook; Nam, Tae-hyun
Abstract: Ti-50.3Ni-0.7Ag (at.%) scaffolds were prepared by sintering of rapidly solidified alloy fibers. The sintered scaffolds possessed high porosity of 80% and large pores of 150–600 μm in size. The yield strength of the scaffold after annealed at 723 K for 3.6 ks was about 2.4 MPa. Ti-Ni-Ag scaffolds had an elastic modulus of 0.8 GPa, similar to that of spongy bone, and exhibited good superelasticity with total recovery strain of 3.4% when 4% pre-strain was loaded at human body temperature. Stable superelastic behavior with complete shape recovery was observed during cyclic deformation in scaffolds. Graphical abstract: Sintered Ti-Ni-Ag scaffolds possessed high porosity of 80% and large pores with size of 150–600 μm. The yield strength of the scaffold after annealed at 723 K for 3.6 ks was about 2.4 MPa. Ti-Ni-Ag scaffolds had an elastic modulus of 0.8 GPa, similar to that of spongy bone, and exhibited good superelasticity with superelastic recovery strain of 2.8% when 4% pre-strain was loaded at human body temperature. Those results would be available for applying Ti-Ni-Ag alloy scaffolds to replace damaged bones.Unlabelled Image